A randomized study of consolidation chemo-radiotherapy versus observation after first-line chemotherapy in advanced gall bladder cancers (RACE-GB Study): trial protocol - Agrawal, Sushma; Singh, Ashish; Rahul; Mishra, Prabhakar; Saxena, Rajan (International Journal of Clinical Trials, 2023)
Background: Chemotherapy (CT) is the standard of care for advanced gall bladder cancer (GBC). However, after completion of 6 cycles of CT, a proportion of patients with good performance status progress within a few months. Retrospective data in locally advanced cases revealed that consolidation chemo-radiotherapy (CTRT) in responders to CT and with good performance status improves overall survival. Methods: FNA proven advanced GBC with predefined clinical-radiological features will be administered 4 cycles CT (cisplatin-gemcitabine combination). After completion of CT, those in good Karnofsky performance status (KPS) will be randomised to consolidation CTRT versus observation (standard of care). The primary end point of the study is to compare OS between the two arms. The secondary end point is to compare progression free survival (PFS), toxicity, and quality of life between the two study arms. The trial is designed to detect an improvement in 2-year overall survival (OS) from 8% in the control arm to 25% in study arm with 80.0% power at a 0.05 significance level. The resultant sample size to achieve this aim is 140 (70 in each arm) over a duration of 4-5 years with a 10% attrition rate. Accrual has been from January 2019 to October 2022. Conclusions: This trial aims to assess the incremental gain in outcomes with consolidation CTRT versus observation in responders to first-line CT in advanced GBCs. This is the first randomised study to evaluate role of consolidation chemoradiation. Trial Registration: The trial is registered with clinical trials registry India (CTRI/2019/04/025204) and clinical trials.gov (NCT05493956).